Nalar Fikih Kebangsaan K.H. Afifuddin Muhajir: Islam, Pancasila dan Keindonesiaan - Mutho’am, Mutho’am; Bashori, Akmal (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Indonesia is not an Islamic country, but Indonesia is also not anti-Islamic. Pancasila positions monotheism in its first principle in line with Islamic theology. Likewise, in the Constitution, it is stated "the blessing of God's grace". However, there are quite a few who consider Indonesia to be thoghut. Kiai Afifuddin Muhajir in this context provides a scientific-fiqhiyyah argument that what Indonesia is accused of being a thoghut state is not correct. So what is Kiai Afifudin Muhajir's concept of national jurisprudence? What is the epistemic-methodical framework of Kiai Afifudin Muhajir's thinking? Based on these questions, this writing uses qualitative research with Karl Menheim's sociology of science approach. The results of the research state that Kiai Afif's national jurisprudence thoughts have a summa-comprehensive reach, including religion-state symbiosis, democracy-public benefit, justice and legal certainty, the appointment of leaders, Pancasila and Islam. Apart from that, research also states that in formulating his thoughts, Kiai Afif has a moderate style of thinking, namely combining nuṣūṣ al-sḥarī'ah with Maqāṣidiyah reasoning. Kiai Afif uses fiqhiyyah and uṣūliyah reasoning, especially in the aspect of people's benefit, and juxtaposes that the issue of the form of the Pancasila state is included in the mu'amalah category, basically, it is a problem of murlahah, which is definitively not prohibited by the Shari'a. Keywords: National Jurisprudence; Fiqh Reasoning; K.H. Afifuddin Muhajir Abstrak Indonesia bukan negara Islam, namun Indonesia juga tidak antipatif terhadap Islam. Pancasila memosisikan monoteistik dalam sila pertamanya selaras dengan teologi Islam. Demikian juga dalam UUD, disebutkan “berkat rahmat Allah”. Meski demikian tidak sedikit yang menganggap Indonesia sebagai thoghut. Kiai Afifuddin Muhajir dalam konteks ini memberikan argumentasi secara ilmiah-fiqhiyyah bahwa apa yang dituduhkan Indonesia negara thoghut adalah kurang tepat. Lantas bagaimana konsep fikih kebangsaan Kiai Afifudin Muhajir? Bagaimana kerangka Epistemik-metodis pemikiran Kiai Afifudin Muhajir? Dari pertanyaan tersebut penulisan ini menggunakan penelitian kualitatif dengan pendekatan sosiologi ilmu pengetahuan Karl Menheim. Hasil penelitian menyatakan bahwa pemikiran fikih kebangsaan Kiai Afif mempunyai daya jangkau summa-komprehensif, meliputi simbiosis agama-negara, demokrasi-kemaslahatan umum, Peradilan dan kepastian Hukum, pengangkatan pemimpin, Pancasila dan keislaman. Selain itu penelitian juga menyatakan bahwa dalam merumuskan pemikirannya Kiai Afif mempunyai corak berpikir moderat yakni menggabungkan nuṣūṣ al-sḥarī’ah dengan nalar Maqāṣidiyah. Kiai Afif menggunakan nalar fiqhiyyah dan uṣūliyah khususnya dalam aspek kemaslahatan rakyat, dan menyandingkan bahwa persoalan bentuk negara Pancasila adalah termasuk dalam kategori mu’amalah pada dasarnya adalah maslaḥah mursalah, yang secara definitif tidak dilarang oleh syariat. Kata Kunci: Fikih Kebangsaan; Nalar Fikih; K.H. Afifuddin Muhajir